IMPLIKASI STRUKTUR USIA TENAGA PENDIDIK TERHADAP KUALITAS PENDIDIKAN: STUDI KASUS DI PROVINSI BANTEN, DKI JAKARTA, JAWA TENGAH, DAN SUMATERA SELATAN - Humaidah; Rolen Hardi Irawan Zai; Bayu Samudra; Naufal Dhika Alriansyah; Julia Postelia Wea Buro (CV. Multi Kreasi Media, 2024)
This study examines the effect of the age structure of the teaching force on education quality in four provinces in Indonesia. Quantitative data for 2023/2024 was analyzed to find the relationship between the age of the teaching force and education quality indicators, such as average national exam scores and graduation rates. The results show that a balance between young and senior educators contributes positively to improving education quality. Younger educators are usually quicker to adapt to technology while senior educators have more extensive teaching experience. This study recommends the need for policies that support the professional development of educators according to their age and current educational needs.